2020
DOI: 10.1097/cmr.0000000000000657
|View full text |Cite
|
Sign up to set email alerts
|

Conception and viable twin pregnancy in a patient with metastatic melanoma while treated with CTLA-4 and PD-1 checkpoint inhibition

Abstract: The treatment of cancer during pregnancy presents a unique challenge. Optimal treatments are often altered or even delayed to protect fetal growth and organogenesis. The landscape of cancer treatment has shifted dramatically over the past several years and treatment with checkpoint inhibitors, including anti-PD1 and anti-CTLA-4 agents has revolutionized treatment outcomes for patients across numerous tumor types. Until recently, little is known about the use of checkpoint inhibitor therapy during pregnancy; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 5 publications
1
55
0
3
Order By: Relevance
“…Additionally, ICI therapy is considered category D in pregnancy, and evidence from solid organ transplant recipients indicates that the risk of fetal malformation is greatly increased if patients are exposed to immunosuppressives such as mycophenolate, 34 35 which are commonly used to manage irAEs. While three isolated case reports have been published of successful pregnancies carried to term while on ICI therapy for metastatic melanoma, [36][37][38] adherence to pregnancy prevention is strongly encouraged during treatment. Managment for irAEs also differs from those for AEs with conventional cancer therapies.…”
Section: General Recommendationsmentioning
confidence: 99%
“…Additionally, ICI therapy is considered category D in pregnancy, and evidence from solid organ transplant recipients indicates that the risk of fetal malformation is greatly increased if patients are exposed to immunosuppressives such as mycophenolate, 34 35 which are commonly used to manage irAEs. While three isolated case reports have been published of successful pregnancies carried to term while on ICI therapy for metastatic melanoma, [36][37][38] adherence to pregnancy prevention is strongly encouraged during treatment. Managment for irAEs also differs from those for AEs with conventional cancer therapies.…”
Section: General Recommendationsmentioning
confidence: 99%
“…These results indicated that Tim‐3 and CTLA‐4 pathways regulated maternal‐fetal crosstalk so to play important role in the maintenance of NP. Thus, though it was reported that conception and viable twin pregnancy in a patient with metastatic melanoma while treated with CTLA‐4 and programmed cell death‐1 (PD‐1) checkpoint inhibition, 23 reproductive safety must be considered, especially when these therapies are used during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint therapy for pregnancy is well discussed as one of the important problems and requires difficult decisions in both the malignancy carrier's (the mother's) health and the fetus' development. Several cases reported the efficacy of anti-PD-1 antibody treatment during pregnancy without influencing mother and fetus growth [20,21]. However, nivolumab is a human IgG4 monoclonal antibody [22] that easily passes through the placenta and can reach the fetus.…”
Section: Discussionmentioning
confidence: 99%